Intraoperative electron radiation therapy combined with external beam radiation therapy and limb sparing surgery in extremity soft tissue sarcoma: a retrospective single center analysis of 183 cases - Röder, Falk; Lehner, Burkhard; Saleh-Ebrahimi, Ladan; Hensley, Frank W.; Ulrich, Alexis; Alldinger, Ingo; Mechtersheimer, Gunhild; Huber, Peter E.; Krempien, Robert; Bischof, Marc; Debus, Jürgen; Uhl, Matthias (Radiotherapy and oncology, 2016)
To report our experience with limb-sparing surgery, IOERT and EBRT in extremity STS.